2022
DOI: 10.22487/j24428744.2022.v8.i1.15800
|View full text |Cite
|
Sign up to set email alerts
|

Review: Medication Error in Prescribing and Dispensing Phases on Outpatient

Abstract: Background: A medication error is defined as "any preventable event that may cause or lead to inappropriate medication use or patient harm while the medication is in the control of the healthcare professional, patient, or consumer." A medication error might occur at any point during the medication-use process, such as when prescribing the medicines, during dispensing, and when the drug is taken by the patient. Objectives: This review focusing on the types of medication errors (MEs) which commonly occurs during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, this process is still assisted by one pharmaceutical technical staff. Pharmacists must carry out even the stages of verification and review of prescriptions because they prevent medication errors from occurring (Anwar et al, 2022). One of the studies at the Pertamina Dumai Hospital in 2019 found a high probability of medication errors occurring due to the error of the pharmacist assistant in interpreting the doctor's prescription, causing fatal consequences for the patient (Mulac et 2021).…”
Section: Prescription Reviewmentioning
confidence: 99%
“…However, this process is still assisted by one pharmaceutical technical staff. Pharmacists must carry out even the stages of verification and review of prescriptions because they prevent medication errors from occurring (Anwar et al, 2022). One of the studies at the Pertamina Dumai Hospital in 2019 found a high probability of medication errors occurring due to the error of the pharmacist assistant in interpreting the doctor's prescription, causing fatal consequences for the patient (Mulac et 2021).…”
Section: Prescription Reviewmentioning
confidence: 99%